Evaluation of musculoskeletal disorders in a food production line. Compared analysis of posture and work activity using 4 methods (2013)
Objective: To compare four methods of evaluating musculoskeletal disorders in order to determine how to carry out the job evaluation process. Material and method: A comparative study of four works stations in the packing process based on an analysis with the methodologies Ovako Working Posture Analyzing System (OWAS), Occupational Repetitive Action (OCRA) check list index and VIDAR was performed. Results: Work station No. 1 obtained a score on OWAS 1 indicating normal posture, OCRA indicated high risk and VIDAR showed four risk positions. Station No. 2 had a score of 2 on OWAS indicating a position with the possibility of causing damage, high risk in OCRA and VIDAR showed an alert for three risk positions. Station No. 3 obtained a score of 1 on OWAS, high risk in the OCRA and VIDAR alerted to five positions of risk. Station No. 4 had a score of 1 for the OWAS, OCRA showed high risk and VIDAR indicated four positions of risk. Discussion: The OWAS and OCRA methodologies are able to quantify the risk that a worker has, VIDAR presents qualitative results, but it takes the worker perception in account. Future developments: It is necessary to use an analysis that identifies risks in the evaluation of work stations. After, methodologies should be used to define the risk and then the VIDAR should be applied to link the source of risk with the perception of the worker. © 2012 Asociación Española de Fisioterapeutas.